INTERAÇÕES CRIANÇA-ANIMAL E INTERVENÇÕES ASSISTIDAS POR ANIMAIS: CONSTRUÇÃO E VALIDAÇÃO DE INSTRUMENTOS DE MENSURAÇÃO - Gomes, Crystian Moraes Silva (2022)
The concept of Human-Animal Interaction (HAI) is widely used to describe the outcome of the different amounts and qualities of interactions between humans and nonhuman animals, including but not limited to pet ownership, contact, bonding, and affection between a human and a nonhuman animal, and Animal-Assisted Interventions (AAI). Children can form close and complex emotional connections with their pets, promoting positive implications for child development, such as increased compassion, empathy, and pro-social behavior. This PhD Thesis aimed to build a theoretical and methodological framework to evaluate child-animal interactions in different contexts, and particularly in AAI. For this, three independent studies were proposed. In the first article, a scoping review on Animal-Assisted Interventions in Latin America was developed, and the methodological quality of the studies considered clinical was evaluated. The results indicated an increase in scientific production in the area, centralization of studies in Brazil and their use in the child population; however, the clinical studies analyzed presented important methodological weaknesses, such as small samples, lack of control group and absence of specific evaluation instruments to measure human-animal interactions. The second article presents the process of construction and initial validation of the Scale of Children's Interest in Pets (EIIAE), for use with Brazilian children aged 2 to 12 years old. The results indicated satisfactory psychometric evidence regarding its internal structure, composed of two factors ("affective interest" and "disinterest and aggressiveness"), for measuring the interest of this population in different animals. In the third article, we sought to explore additional validity evidence for the Child-Dog Interaction Scale (EICC) for use with Brazilian children aged 2 to 12 years. The results indicated that the bifactor structure ("affective interaction" and "educational and punitive interaction"), is a robust structural model to measure the interaction between children and domestic dogs. The three studies presented allow us to understand that despite the importance of child-animal interactions for child development, in Latin America the use of standardized and validated methodologies to measure the different interactions of children with pets is incipient. The results of this Thesis may contribute to the construction of an empirical basis for the field of AAI in Brazil, as well as assist in the process of selection/screening, and planning of sessions of Animal-Assisted Interventions for child population.